2001
DOI: 10.1107/s0909049500014564
|View full text |Cite
|
Sign up to set email alerts
|

X-ray-excited optical luminescence of impurity atom in semiconductor

Abstract: We observed the x-ray-excited optical luminescence (XEOL) of erbium-doped silicon (Si:Er) thin films to make a site-selective x-ray absorption fine structure (XAFS) measurement of an optically active Er atom. The undulator beam was used for the increment of the electron population in the excited state, and following XEOL at an infrared wavelength of 1.54 µm with minimum absorption loss in the host Si was detected. The edge-jump and XAFS oscillation were successfully obtained at the Er L III -edge. This spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, to the best of our knowledge, a detailed discussion on Ho L 1 -edge XANES spectra is not known. Erbium has much wider application than holmium as a dopant for laser devices, and its L 3 -edge XANES studies have been reported elsewhere. For example, Ishii et al measured the Er L 3 -edge XANES spectra of Er 2 O 3 and Si:Er 2 O 3 thin film prepared by a laser ablation method to investigate the optical activation process of Er and found the second derivatives of the Er L 3 -edge XANES spectra exhibit two minima related to the split 5d orbitals induced by the local configuration of Er . Yb L-edge XANES spectra were also used to investigate the local structure of Yb in various materials. Lanthanide L 1 -edge XANES spectra have been rarely reported, but Quartieri et al used Yb L 1 - and L 3 -edge XANES spectra of synthetic pyrope and grossularite garnets for structural analysis in combination with full multiple scattering calculations .…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, a detailed discussion on Ho L 1 -edge XANES spectra is not known. Erbium has much wider application than holmium as a dopant for laser devices, and its L 3 -edge XANES studies have been reported elsewhere. For example, Ishii et al measured the Er L 3 -edge XANES spectra of Er 2 O 3 and Si:Er 2 O 3 thin film prepared by a laser ablation method to investigate the optical activation process of Er and found the second derivatives of the Er L 3 -edge XANES spectra exhibit two minima related to the split 5d orbitals induced by the local configuration of Er . Yb L-edge XANES spectra were also used to investigate the local structure of Yb in various materials. Lanthanide L 1 -edge XANES spectra have been rarely reported, but Quartieri et al used Yb L 1 - and L 3 -edge XANES spectra of synthetic pyrope and grossularite garnets for structural analysis in combination with full multiple scattering calculations .…”
Section: Introductionmentioning
confidence: 99%